Novel findings deduced from the microscopic kinetics model contest the classical nucleation theory - Xu, Jun (Frontiers in Soft Matter, 2023)
We revisit the microscopic kinetics model considering crystal nucleation as reversible attaching and detaching of units from growing clusters. Based on the variation of the rate constants of attaching and detaching with cluster size, we derive some findings that contest the classical nucleation theory. First, the equivalent thermodynamic parameters are deduced from the rate constants, which reveal that the interfacial free energy per area varies with cluster size and finally levels off. Second, if the crystal is not perfect, at the melting point, the nucleation barrier will be definite rather infinitely large. Third, it is predicted that the critical nuclei size does not vary with supersaturation. Fourth, when the neighboring units from the same polymer chain are used for crystal nucleation, the attaching rate constant should decrease with cluster size, which is distinctly different from the same attaching rate constant in nucleation of small molecular crystals. These interesting findings show that teaching the old dog (microscopic kinetics model) new tricks could get new findings and deepen our understanding of crystal nucleation.